The Impact of Informal Employment of the Population of the Northern Resource-Producing Region on Its Budget - Khromtsova, Lina Sergeevna; Burundukova, Elena Mikhaylovna; Osipova, Viktoria Sergeevna (Economy of Regions, 2020)
It is currently impossible to analyse the socio-economic situation and the budgets of the Russian regions without taking into account the problems of informal employment. There is a wide variety of publications on this topic. However, they do not sufficiently address the regional features and reasons for the behaviour of economic entities, which do not wish to comply with the legalization requirements. We conducted the research based on the neoliberal concept, which considers the informal sector as a consequence of the excessive regulation and state taxation. We hypothesise that the existence of informal employment in the region results in a budget deficit and requires the development of measures promoting the legalization of self-employed income. The study determined the level and causes of the regional informal employment, and assessed its impact on the budget. As a research methodology, we applied empirical methods, statistical, economic and financial analysis. The survey of the population of the Khanty-Mansy Autonomous Okrug — Yugra, established the nature and the main causes of informal employment. Based on the analysis of the regional budget and labour resources, we have examined the impact of informal employment on the budget and determined its cumulative effect. Finally, we have proposed a methodology for assessing how the existing level of self-employment influences the regional budget. This methodology takes into account not only the damage caused to the regional budget revenue due to the lack of tax payments, but also the damage associated with excessive social expenditures on the self- employed population. The research results can be used for developing the projects aimed at reducing informal employment at all levels of government.